Analysis of Vibration Reduction Properties of Rail Damping under High-Speed Vehicle Moving Load. (March 2014) - Cui, Rixin; Gao, Liang; Zhong, Yanglong; Xin, Tao
Rail damping is an active and effective control method for mitigating railway vibration and noise at the source. In order to investigate the applicability of rail damping to high-speed railway, a vehicle-ballastless slab track-bridge coupling dynamic model was established and the vibration reduction effect of rail damping at bridge mid-span, bridge pier and beam gap under a high-speed vehicle moving load was analyzed. The results show that: the max vibration acceleration of ballastless track and bridge with rail damping are obviously decreased, and the duration time of structure vibration is also shortened. The vibration reduction effect of rail damping at bridge mid-span is more significant than that at bridge pier. In the working frequency range of rail damping, the acceleration vibration level of the rail can be reduced by 2–5dB, and the vibration of ballastless track slab and bridge also can be decreased in middle and high frequency range.